Lard uptake and its detection in selected food products deep-fried in lard - Marikkar, Mohammed Nazrim; Ghazali, H.M.; Long, K.; Lai, O.M. (Elsevier, 2003)
Lard uptake and its detection in selected food products deep-fried in lard. Food Res. Int., 36 (9): 1047–1060 (2003). Analytical methods for the detection of both pork and lard in food products are in great demand for regulatory purposes. Means of identifying food products fried in lard has been investigated in this study. Four fat containing products namely, peanuts, tempeh (fermented soybean cake), chicken and beef were subjected to deep-fat frying using lard as the frying medium. Oils extracted from the control and fried samples were analyzed by gas liquid chromatography (GLC), high performance liquid chromatography (HPLC) and differential scanning calorimetry (DSC). In this way, changes in composition and thermal profiles during frying were examined. Results showed that palmitic acid enrichment factor (PAEF) calculated from GLC analysis of fatty acid methyl esters seems to be a useful parameter in determining lard contamination in all four fried products. With the triglycerol (TG) profiling by HPLC it was possible to detect lard in fried chicken and tempeh products while DSC cooling and heating traces were found to be useful for lard detection in fried tempeh, chicken and beef products.